Responsible alcohol service: lessons from evaluations of server training and policing initiatives - Stockwell, Tim (Taylor and Francis, 2001)
Responsible alcohol service programmes have evolved in many countries alongside a general increase in the availability of alcohol and a greater focus on the prevention of alcohol-related road crashes. They also recognize the reality that a great deal of high-risk drinking and preventable harm occurs in and around licensed premises or as drinkers make their way home. Early US efficacy studies of programmes which trained managers and barstaff to limit customers' levels of intoxication and prevent drink driving showed promise. Studies of effectiveness of these programmes in the wider community, and in the absence of the enforcement of liquor laws, found little benefit. The data will be interpreted as suggesting that, in reality, skills deficits in the serving of alcohol are not a significant problem compared with the motivational issue for a commercial operation of abiding by laws that are rarely enforced and which are perceived as risking the goodwill of their best customers. Australian, UK and US experiences with liquor law enforcement by police will be discussed along with outcomes from the Australian invention of Alcohol Accords, informal agreements between police, licensees and local councils to trade responsibly. It will be concluded that the major task involved in lifting standards of service and preventing harm is to institutionalize legal and regulatory procedures which impact most on licensed premises. A number of strategies are suggested also for creating a political and social climate which supports the responsible service of alcohol and thereby supports the enactment and enforcement of appropriate liquor laws.